Quantifying the Role of Ocean Dynamics in Ocean Mixed Layer Temperature Variability - Patrizio, Casey R.; Thompson, David W. J. (Journal of climate, 2021)
Understanding the role of the ocean in climate variability requires first understanding the role of ocean dynamics in the ocean mixed layer and thus sea surface temperature variability. However, key aspects of the spatially and temporally varying contributions of ocean dynamics to such variability remain unclear. Here, the authors quantify the contributions of ocean dynamical processes to mixed layer temperature variability on monthly to multiannual time scales across the globe. To do so, they use two complementary but distinct methods: 1) a method in which ocean heat transport is estimated directly from a state-of-the-art ocean state estimate spanning 1992–2015 and 2) a method in which it is estimated indirectly from observations between 1980–2017 and the energy budget of the mixed layer. The results extend previous studies by providing quantitative estimates of the role of ocean dynamics in mixed layer temperature variability throughout the globe, across a range of time scales, in a range of available measurements, and using two different methods. Consistent with previous studies, both methods indicate that the ocean-dynamical contribution to mixed layer temperature variance is largest over western boundary currents, their eastward extensions, and regions of equatorial upwelling. In contrast to previous studies, the results suggest that ocean dynamics reduce the variance of Northern Hemisphere mixed layer temperatures on time scales longer than a few years. Hence, in the global mean, the fractional contribution of ocean dynamics to mixed layer temperature variability decreases at increasingly low frequencies. Differences in the magnitude of the ocean dynamical contribution based on the two methods highlight the critical need for improved and continuous observations of the ocean mixed layer